Birthing partners - validation of a questionnaire to assess the well-being of support persons - Nadine Schmitt; Juliane Lamprecht; Sabine Striebich; Gabriele Meyer (BMC Pregnancy and Childbirth)
Abstract Background There is little research on the well-being of the persons giving support during childbirth and how they feel when doing this. The aim of this study is to validate a questionnaire that assesses the well-being of those support persons during childbirth. This publication focuses on the validation of the questionnaire; the development is described in more detail in a previous publication. Methods After the questionnaire had been developed, it was sent online to a sample for validation. Subsequently, the internal consistency was determined to assess the reliability and the correlation with an external criterion in order to assess the criterion validity. Known-groups validation was used to assess the construct validity of the questionnaire. Linear regressions were carried out to analyse which variables influence well-being. Results The results show good reliability and high criterion validity. The known-groups analyses identified group differences between the different birth modes regarding the different domains of well-being of the support persons. Factors influencing well-being are whether it is a first time or repeated support, whether the birthing woman is a primiparous or multiparous woman and whether the birth is vaginal or operative. Conclusion Our results suggest that this questionnaire adequately captures important aspects of the well-being of support persons during childbirth. The questionnaire is designed for all birth experiences. In the case of negative experience it can be used to assess additional support and counselling and thus potentially promote the mental health of the support persons preventively.